Response Surface Methodology Approach to Predict the Flexural Moment of Ferrocement Composites with Weld Mesh and Steel Slag as Partial Replacement for Fine Aggregate - Jayaprakash Sridhar; Ganesh Bhausaheb Shinde; D Vivek; Khalida Naseem; Piyush Gaur; Pravin P Patil; Misganaw Tesfaye Tesema (Advances in Materials Science and Engineering)
Design of Experiment-Response surface methodology approach is adopted to obtain the optimal flexural moment of ferrocement composites comprising galvanised square weld mesh with weight fraction of fine aggregate by steel slag. To get the optimal combination of progression variables on a flexural moment of ferrocement composites, the central composite design of response surface methodology was adopted. Regression models for responses were justified using analysis of variance and the Pareto chart. The test results show that a maximum ultimate load of 3.30 kN and moment capacity of 220 kNm was obtained for ferrocement with a volume fraction of 2.733% and steel slag of 25% replacement. From the analysis of variance, it is evident that the p value is less than 0.005, the predicted R2 and the adjustable R2 are less than 20%, and the predicted values go in hand with the experimental result which indicates that the proposed models are highly suitable. Moreover, the volume fraction of galvanised square weld mesh has a higher significance on a flexural moment of ferrocement composites. Surface plot, Pareto chart, and regression analysis outcomes show that the most substantial and influential factor for a flexural moment is the volume fraction of galvanised square weld mesh.